1992
DOI: 10.1111/j.1570-7458.1992.tb00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of mycotoxins of Fusarium sambucinum for feeding in Galleria mellonella

Abstract: Fusarium sambucinum Fuckel showed antifeedant activity towards larvae of Galleria mellonella L. when incorporated into insect diet. The activity appeared mostly due to the concentration of trichothecenes present in the fungal extracts. Diacetoxyscirpenol and neosolaniol showed similar levels of activity and were significant potent antifeedants against larvae at 50 and 100 ppm. On the contrary, enniatin B showed no activity up to 100 ppm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Several secondary metabolites from Fusarium spp. have been shown to have insecticidal activity and therefore may play a role in G. mellonella larvae killing (Claydon et al 1977, 1979; Mule et al 1992; Strongman et al 1988). In addition, the morphology of the conidia was important for virulence in this pathosystem (Fig 3), however the precise mechanism conferring the higher virulence of macroconidia is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several secondary metabolites from Fusarium spp. have been shown to have insecticidal activity and therefore may play a role in G. mellonella larvae killing (Claydon et al 1977, 1979; Mule et al 1992; Strongman et al 1988). In addition, the morphology of the conidia was important for virulence in this pathosystem (Fig 3), however the precise mechanism conferring the higher virulence of macroconidia is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, compounds that restrain aphids from feeding may reduce direct insect damage to crops and indirect damage due to infection with insect-transmitted viruses (Pickett et al 1987). Data on such effects of fungal metabolites towards insect pests are limited (Wright et al 1982;Mulè et al 1992;Amiri et al 1999;Ekesi et al 2001;Ganassi et al 2007). Ganassi et al (2007) showed that some fungal isolates of the genus Trichoderma influenced the feeding preference of Schizaphis graminum, one of the most important pests of cereal crops, suggesting a potential antifeedant activity of these fungi towards aphids.…”
Section: Introductionmentioning
confidence: 97%
“…These mycotoxins are non-ribosomal peptides and can be classified into chain peptides or cyclic peptides based on their chemical structure. A number of toxins have been reported from different entomopathogenic fungi, some of them include destruxins (Pedras et al 2002;Liu and Tzeng 2012), bassianolides (Suzuki et al 1977), beauvericins (Wang and Xu 2012), enniatins (Mule et al 1992;Hiraga et al 2005), efrapeptins (Lardy et al 1975) and so on. Chapters 8-11 of this volume provide more details on these mycotoxins.…”
Section: Entomopathogenic Fungimentioning
confidence: 99%